2012
DOI: 10.1212/wnl.0b013e3182698c64
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying drugs for multiple sclerosis in pregnancy

Abstract: Further studies are needed to determine the potential risks associated with preconceptional and in utero DMD exposure in patients with MS. Discontinuation of DMDs before conception is still recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 31 publications
4
114
1
2
Order By: Relevance
“…It is thought to activate regulatory T-cells that recognize the myelin basic protein antigen. Similar to IFN, GA does not seem to affect the rate of conception nor the rate of spontaneous abortion when compared to women without MS, and no major concerns have been reported when GA has been used in pregnancy [22]. Women who have used GA during breast-feeding report no adverse effects, although it is still recommended to abstain from GA during lactation [24].…”
Section: Effect Of Dmt On Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…It is thought to activate regulatory T-cells that recognize the myelin basic protein antigen. Similar to IFN, GA does not seem to affect the rate of conception nor the rate of spontaneous abortion when compared to women without MS, and no major concerns have been reported when GA has been used in pregnancy [22]. Women who have used GA during breast-feeding report no adverse effects, although it is still recommended to abstain from GA during lactation [24].…”
Section: Effect Of Dmt On Pregnancymentioning
confidence: 98%
“…In clinical trials comparing IFN therapy to placebo, IFN did not affect the rate of conception nor the rate of spontaneous abortion [20,21]. However, IFN exposure was associated with a significantly lower birth weight and preterm birth [22]. The degree and significance of IFN transfer through breast milk has not been established, but it is suggested that IFN be avoided during breast-feeding [23].…”
Section: Effect Of Dmt On Pregnancymentioning
confidence: 99%
“…Even though there is a lack of well-controlled data on pregnancyrelated risks for all DMTs, some data suggest that GA may have the best safety profile among the first-line DMTs with regard to this common patient need. Copaxone received the most favorable Food and Drug Administration (FDA) pregnancy label (category B), but data are considered insufficient and further research seems necessary [13].…”
Section: Gamentioning
confidence: 99%
“…If the patient is concerned about rare and maybe even not-yet-known adverse effects, the injectables might be a good choice because of the years of experience with these drugs. Also, women with child-bearing potential that plan to become pregnant, or at least keep open the possibility of becoming pregnant, may also opt for the injectables (in particular GA [13]). Women that are planning to become pregnant should probably not use teriflunomide.…”
Section: Initiation Of Therapymentioning
confidence: 99%
“…The primary population typically affected by MS comprises young women who nowa days receive assurances that pregnancy will not have a de leterious effect on the disease 1 . However, the withdrawa l of all MS medications is recommended to women who choose to become pregnant or experience an unplanned pregnancy 2 . In fact, it is recommended that a woman who does not make use of effective methods of contraception should not be treated for MS.…”
mentioning
confidence: 99%